The Effect of Auditor Turnover, Financial Distress, and Audit Delays on Audit Quality in Pharmaceutical Manufacturing Companies Listed on the Indonesia Stock Exchange (2020-2023) - Ryan Putra Hafikar Suardi; Marwah Yusuf; Dahniyar Daud (Manunggal Halim Jaya, 2026)
This study examines the influence of auditor switching, financial distress, and audit delay on audit quality in pharmaceutical manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. The issue of audit quality gained heightened attention following the investigative findings of Indonesia’s Supreme Audit Board (BPK) on PT Indofarma Tbk, which revealed significant financial irregularities despite the issuance of clean audit opinions by the same public accounting firm. Using a quantitative approach and secondary data obtained from audited annual reports, the study analyzes 44 firm-year observations drawn from 11 companies that met the sampling criteria. Logistic regression is employed to evaluate whether the independent variables significantly influence the likelihood of receiving a high-quality audit, measured through Big Four affiliation. The findings show that auditor switching and audit delay do not significantly affect audit quality, indicating that changes in audit firms and variations in audit completion time do not determine the rigor of audit outcomes. Conversely, financial distress demonstrates a significant negative effect, suggesting that firms facing higher financial pressure receive lower audit quality, potentially due to increased risk perceptions and stricter auditor scrutiny. These results contribute to the literature by providing updated empirical evidence from a highly regulated and vulnerable industrial subsector. The study offers theoretical reinforcement for agency theory and practical insights for regulators, auditors, and corporate management regarding factors that may influence audit quality reliability.